A matrix approach to visually communicate simultaneously the environmental and health impacts of foods - Berardy, Andrew; Fresán, Ujué; Abbaspour, Nazanin; Sabaté, Joan (Frontiers in Nutrition, 2025)
IntroductionDespite an unprecedented wealth of knowledge regarding the environmental and health effects of foods, no studies effectively and simultaneously communicate both characteristics in an easily comprehensible visual format. This work, therefore aims to provide a clear visualization that intuitively demonstrates the relative characteristics of a comprehensive list of foods to encourage more informed decision-making across stakeholders.MethodsData are aggregated from meta-analyses and reviews regarding the carbon footprint (CFP) and health effects of 30 food groups commonly consumed in the United States of America. The data are then used to categorize food groups as favorable, neutral, or unfavorable to health and as having a low, medium, or high carbon footprint. These classifications are then used to arrange food groups into a three by three color-coded matrix.ResultsThe resulting visualization simultaneously communicates environmental impacts and health implications of food groups in a single figure. Overall, the visualization indicates plant-based and less processed foods are preferable to animal-based and more processed foods. An exception to the format is made to emphasize the exceptionally large carbon footprint of beef by splitting the lower-right cell into two halves.DiscussionClassification of food groups according to health effects and carbon footprint is consistent with results presented in other studies. The color-coded matrix format quickly and intuitively communicates the tradeoffs made when choosing between different food groups, which may help improve choices for human and planetary health.